Reprywatyzacja w świetle zasad prawa: [Reprivatisation in light of the rules of law] (Studia Prawnicze / The Legal Studies, 2015)
Roszczenia reprywatyzacyjne dzielą się na dwie grupy. Pierwsza z nich kwestionuje ciągłość prawną między Polską Rzeczpospolitą Ludową i III Rzeczypospolitą. PRL jako państwo niesuwerenne miało stanowić „czarną dziurę” w historii polskiej państwowości. Stąd jego akty nacjonalizacyjne i wywłaszczeniowe mające na celu odbudowę kraju ze zniszczeń wojennych i jego rozwój zgodny z zasadami sprawiedliwości społecznej należy uznać za nieważne i zwrócić własność byłym właścicielom. Własność prywatna jest nienaruszalna i powinna być restaurowana.Druga grupa roszczeń uznaje co prawda ciągłość prawną między Polską Rzeczpospolitą Ludową a III Rzeczpospolitą, ale twierdzi, że wszystkie decyzje nacjonalizacyjne i wywłaszczeniowe rażąco naruszały prawo i dlatego w trybie postępowań nadzorczych powinny być unieważniane.Roszczenia I i II grupy znalazły wsparcie w działaniach państwowego IPN zwalczającego „zbrodnie komunistyczne” i „komunistyczne bezprawie” oraz w programach partii, które uznają powojenną nacjonalizację za grabież nienaruszalnej własności prywatnej, oraz w uchwałach Senatu potępiających regularnie „wynaturzony” PRL.Z uwagi na skalę rozszerzających się roszczeń reprywatyzacyjnych (już w tej chwili w przybliżeniu szacowanych nawet na 250 miliardów złotych) powstał specjalny „byznes”, wokół którego narosły liczne patologie (oszustwa, fałszerstwa, wyłudzenia itp.).Presja spadkobierców byłych właścicieli i nabywców ich roszczeń wsparta przez zasygnalizowane działania polityczno-ideologiczne wpłynęła niestety na kierunki orzecznictwa administracyjnego i sądowego. Zanegowano w nim sens instytucji zasiedzenia (art. 172 Kodeksu cywilnego) poprzez przyjęcie, że okres PRL stanowił „siłę wyższą” (art. 121 pkt 4 w związku z art. 172 Kodeksu cywilnego), która uniemożliwiała rozpoczęcie biegu przedawnienia lub go przerywała. Stąd państwo polskie nie mogło zasiedzieć znacjonalizowanych lub wywłaszczonych nieruchomości. Sądy cywilne zasądzają zwroty w naturze albo odszkodowania według zasad Kodeksu cywilnego za utracone nieruchomości.Z kolei sądy administracyjne zaczęły unieważniać, w sposób nieograniczony żadną cezurą czasową, decyzje wywłaszczeniowe, nacjonalizacyjne i w ten sposób uruchamiać postępowania przed sądami cywilnymi o odszkodowania od Skarbu Państwa. Sądy administracyjne unieważniając decyzję, przyjęły niezgodną z Konstytucją z 1997 r. wykładnię art. 156 § 1 pkt 2 in fi ne w związku z § 2 k.p.a. Niezgodną, bo nieograniczoną żadną cezurą czasową.Prowadzone obecnie działania reprywatyzacyjne o stale rozszerzającej się skali i coraz większych związanych z nimi patologiach oparte są więc na wadliwym rozumieniu obowiązującego prawa. Restitution claims are divided in two groups. One of them questions legal continuity between the Polish People’s Republic and the Third Republic of Poland. As a non-sovereign country, Polish People’s Republic was supposed to become a “black hole” in the history of Polish statehood. Therefore its nationalisation and expropriation acts concerning restoration of the country from war damages and its development according to the principles of social justice should be considered void and the properties returned to their former owners. Private property is inviolable and should be restored.The second group of the claims recognizes legal continuity between Polish People’s Republic and the Third Republic of Poland but predicates that all nationalisation and expropriation decisions grossly violated the law and because of that should be cancelled according to mode supervisory procedures.The claims of both groups were supported by Institute of National Remembrance actions fighting “Communist regime’s crimes” and “Communist lawlessness” as well as in the programmes of the parties which would define postwar nationalisation as the plunder of inviolable private property, and also in Senat’s resolutions which regularly condemned “denaturalized” Polish People’s Republic.The large scale of restitution claims (at this moment they are approximately estimated at 250 billion zlotys) created a special type of “business” which is connected with numerous pathologies (frauds, forgeries, extortions etc.).The pressure coming from former owners’ inheritors and purchasers of their claims supported by signalled political-ideological actions unfortunately has affected the directions of administrative and judicial jurisprudence. It negated the meaning of acquisitive prescription (Civil Code, article No. 172) by assuming that the period of the Polish People’s Republic was force majeure (Civil Code, article No. 121, subparagraph 4 with regard to Civil Code, article No. 172) which made it impossible to start the limitation period or to stop it. Hence the Polish State could not prescribe the nationalised or the expropriated properties. The civil courts adjudge restitutions in kind or compensations for lost estate according to the Civil Code.In turn administrative courts started to cancel expropriating and nationalisating decisions without any censorship time and in this way started to run in civil courts the compensation from the State Treasury procedures. By cancelling these decisions, the administrative courts accepted incompatible with the Constitution interpretation of article 156 section 1 subparagraph 2 in fine with regard to section 2 Code of Administrative Proceedings. Incompatible because not limited with any censorship time.Currently ongoing restitution procedures with constantly growing range and pathologies connected with it are therefore based on incorrect understanding of applicable law.Claims of former owners or their legal successors can only have moral ground (sense of injustice) and because of that it is necessary to confront them with current public functions of estate taken over after the war and with rights of people who in the mean time obtained ownership as well as the possibilities of public finances. After balancing these causes (following the Constitution principles and values) and after having them accessed by a properly prepared referendum after which (with a positive result of it) an act about limited compensation with different subjective exemptions could be prepared.Reprivatisation proceeding today has therefore no legal ground and does a lot of harm. That’s why it should be stopped and settled according to supervisory proceedings.